SURFACTANT THERAPY AND BRONCHOPULMONARY DYSPLASIA DEVELOPMENT IN VERY PRETERM INFANTS - D. Dobryanskyy; O. Borysiuk (Bukovynian State Medical University, 2019)
In a prospective cohort study the association between surfactant therapy and development (severity) of bronchopulmonary dysplasia (BPD) in very preterm infants required mechanical ventilation after birth was studied taking into account infants' age, surfactant dose and particular surfactant preparation use. 88 newborns received surfactant were included into the main group. 29 control newborns were treated according to standard protocols but without surfactant. Early rescue surfactant administration (during the first 2 hrs. of life) was used in 21 (24%) infants. The rest 67 of the babies (76%) got surfactant later, in about 10 hrs. after birth. 24 patients received several surfactant doses, but 64 - only one dose. 31 newborns were treated with Neosurf and 57 infants - Curosurf. Prevalence of majority of perinatal risk factors was similar in the both groups. The study results showed that in newborns required mechanical ventilation after birth, surfactant therapy did not prevent BPD development but did reduce the incidence of air leak syndromes and total duration of mechanical ventilation and could alleviate the severity of lung injury.